Connecting (g − 2) μ to neutrino mass in the extended neutrinophilic 2HDM - A. L. Cherchiglia; G. De Conto; C. C. Nishi (Journal of High Energy Physics, 2023)
Abstract One simple way to lower the scale of the seesaw mechanism that generates neutrino masses is to attribute part of their smallness to a suppressed vacuum expectation value of a second Higgs doublet as in the neutrinophilic 2HDM or in the type IB seesaw model. On that structure we add one charged singlet scalar to induce a chirally enhanced contribution to (g – 2) μ with the same righthanded neutrinos of the seesaw. We discuss the interplay of generating the necessary contribution to the latter with lepton flavor violation which is also necessarily brought to low scale. We show that it is possible to explain (g –2) μ even for heavy neutrino masses of order of a few TeV.